REVIEW: Research Ethnobotany in Indonesia and the Future Perspectives - EKO BAROTO WALUJO (Society for Indonesian Biodiversity, 2008)
Indonesia is not only rich in its biodiversity but it is also well known as a country with high diversity of ethnicities. Each ethnic group has extensive experienced in the utilization and conservation of biological and ecological diversity. This biocultural richness has provided ethnobotanical researchers with endless research opportunities. Ethnobotanical study has a long history in Indonesia and dates back to the early Dutch colonization period when Dutch explorers and naturalists recorded the uses of plants used by the natives for food, medicine, buildings materials, etc. Based on research on Java, Hasskarl (1845) recorded 900 species of plants used by Indonesian communities. Previously, Rumphius (1750) in his monumental book